The relationship between pain level and satisfaction following lumbar spinal stenosis surgery and psychiatric medication use - Ertugrul, Bilal; Komurcu, Harun (Elsevier, 2026)
Background: Lumbar spinal stenosis is a common degenerative spinal disorder that often requires surgery. In addition to technical factors, postoperative pain perception and patient satisfaction are influenced by psychosocial and psychiatric factors. However, the relationship between psychiatric medication use and postoperative outcomes remains unclear. Objective: To examine the association between the use of psychiatric medication, postoperative pain, and patient satisfaction following surgery for lumbar spinal stenosis. Methods: This retrospective cohort study included 202 patients who underwent surgery for degenerative lumbar spinal stenosis. Patients were divided into a psychiatric medication group (n = 98) and a control group (n =104). Pain was assessed using the Visual Analogue Scale preoperatively and at 24 h, one week, and one month postoperatively. Patient satisfaction was evaluated at one month using a 0-10 Likert scale. Results: Postoperative pain scores were significantly higher in patients using psychiatric medication at all time points (p < 0.001). At one month, patient satisfaction was significantly lower in the psychiatric medication group compared to controls (6.3 +/- 1.7 vs. 8.1 +/- 1.4, p < 0.001). Conclusion: Psychiatric medication use was associated with higher early postoperative pain scores and lower short-term patient satisfaction following lumbar spinal stenosis surgery. These findings should be interpreted cautiously, as psychiatric medication use may reflect underlying psychiatric disease burden rather than a direct pharmacological effect.
Keywords: Lumbar spinal stenosis; Postoperative pain; Psychiatric medication; Rehabilitation outcomes